Effectiveness of Two Cold Water Immersion Protocols on Neuromuscular Function Recovery: A Tensiomyography Study - Sánchez-Ureña, Braulio; Rojas-Valverde, Daniel; Gutiérrez-Vargas, Randall (Frontiers in Physiology, 2018)
Cold water immersion (CWI) has become a highly used recovery method in sports sciences, which seeks to minimize fatigue and accelerate recovery processes; however, few studies have used tensiomyography (TMG) is a new method to analyze the muscle mechanical response as a recovery indicator after CWI protocols, this relative new tool of muscle function assessment, can lead to new information of understand fatigue recovery trough CWI. The objective of the study was to compare the effect of two CWI protocols, on neuromuscular function recovery. Thirty-nine healthy males (21.8 ± 2.876 yrs., 73.215 ± 8.215kg, 176.6 ± 5.3 cm and body fat 13.5 ± 3.4%.%) were included in the study. Participants were grouped into a continuous immersion (12 min at 12 ± 0.4 °C) group, intermittent immersion (2 min immersion at 12 ± 0.4 °C + 1 min out of water 23 ± 0.5 °C) group, and a control group (CG) (12 min sitting in a room at 23 ± 0.5 °C). Afterwards, the participants performed eight sets of 30 sec counter movement jumps (CMJ) repetitions, with a 90 s standing recovery between sets. Muscle contraction time (Tc), delay time (Td), muscle radial displacement (Dm), muscle contraction velocity at 10% of DM (V10), and muscle contraction velocity at 90% of DM (V90) in rectus, biceps femoris, and CMJ were measured. Neither CWI protocol was effective in showing improved recovery at 24 and 48 hours after training compared with the CG (p > .05), in any TMG indicator of recovery in either muscle biceps or rectus femoris, nor was the CMJ performance (F(6,111) = 0.43, p = .85, ωp2 = 0). Neither CWI protocol contributed to recovery of the neuromuscular function indicator.